Morphological-sytactical learning problems in English verb phrases on the predicate layer an error analysis - Halili, Adoracion Mamawi 1933- (1978)
This research was undertaken to investigate a number of issues relevant to a theory of second language acquisition. With the interlanguage hypothesis providing the theoretical framework, this study was designed to investigate the errors made by Filipino College freshmen students in the learning of English as a second language. The performance data was culled from the students' written compositions and responses in the translation test. Based on the findings, it is strongly suggested that the methodology in the design of elicitation procedures be further refined and the longitudinal studies on the Filipino learner's language development be further investigated.
Mimeographed.
Thesis (Ph.D.)--University of the Philippines, Quezon City.
Vita.
Keywords: English language -- Morphology; English language -- Study and teaching -- Foreign students; English language -- Syntax